A SCIENTIFIC WORLDVIEW OF ACCOUNTING ETHICS AND GOVERNANCE EDUCATION: THE RIGHT FOOTING OF INTERNATIONAL EDUCATION STANDARD 4, BUT... - Arfah Salleh,; Aziuddin Ahmad, (Asian Academy of Management Journal, 2012)
This paper is a critique of the approach in which the issue of accounting ethics and governance has been tackled through education. In light of the existence of the International Education Standard (IES) 4 specifically on ethics as the relevant framework developed by the International Federation of Accountants (IFAC), the discussion in this paper centres on the requirement of IES 4 and the manner it is suggested for implementation. Based on the ontological and epistemological reality of the world as reflected in science which also parallels religion and Eastern belief system, we are sceptical of the degree of representation of reality of the model of ethics and governance that is currently upheld by accounting curriculum designers. A framework on ethics education that is more holistic is proposed.